The effect of recycling on the oxygen distribution in Ti-6Al-4V powder for additive manufacturing. (4th May 2018) - Sun, Yu; Aindow, Mark; Hebert, Rainer J.
Abstract: Ti-6Al-4V powder has been recycled 30 times in an electron beam melting system. A combination of electron microscopy techniques has been used to show that the recycled powder has a 35% higher oxygen content, and that the particles have a more irregular morphology, a narrower particle size distribution, and a much more variable microstructure than the virgin powder. The microstructures in the recycled powder particles vary from a martensitic α′ structure, which is identical to that in the virgin powder, to a two-phase α + β structure. This variability is related to the complex thermal history of the unmelted metal powder in the system. Despite these differences, all of the particles exhibit essentially the same surface oxide thickness; the excess oxygen in the recycled powders is instead located in the β phase. The possible consequences for the structure and properties of the resultant additively manufactured parts are discussed.